UJI DAYA HAMBAT MADU HUTAN BADUY SEBAGAI SUBSTRAT PADA BUNGA TELANG (Clitoria ternatea L) MELALUI METODE BIOTEKNOLOGI FERMENTASI KOMBUCHA DALAM MENGHAMBAT PERTUMBUHAN BAKTERI PATOGEN - Kusumiyati Kusumiyati; Diyan Yunanto Setyaji; Firman Rezaldi; M. Fariz Fadillah (MEDFARM: Jurnal Farmasi dan Kesehatan, 2022)
Telang flower (Clitoria ternatea L) fermented by kombucha is a probiotic drink produced by a consortium of bacteria and yeast. The raw material in this kombucha fermentation is in the form of telang flowers that have been cold from the previous boiling process. This study aims to determine the antibacterial activity of telang flower kombucha with different concentrations of Baduy forest honey. The concentration of Baduy forest honey consisted of 20%, 30%, and 40% (w/v) where each treatment was repeated 3 times. The positive control used in this study was kombucha made from green tea. Sterile aquadest is a treatment positioned as a negative control. The disc diffusion method is one of the methods used in antibacterial testing by measuring the diameter of the inhibition zone. Telang flower kombucha fermentation has activity as a broad-spectrum antibacterial source. This can be indicated by the potential to prevent the growth of Staphylococcus aureus, Staphylococcus epidermidis, Pseudomnonas aeruginosa, and Escherichia coli bacteria. Baduy forest honey concentration of 40% is the best concentration in fermented kombucha flower telang as an antibacterial and has the potential as the latest functional drink from fermented biotechnology products.